Identification of Patients With COPD in a Cardiac Rehabilitation Setting: THE COnCuR STUDY. Issue 3 (May 2021) - Ozemek, Cemal; Arena, Ross; Rouleau, Codie R.; Campbell, Tavis S.; Hauer, Trina; Wilton, Stephen B.; Stone, James; Laddu, Deepika; Williamson, Tamara M.; Liu, Hongwei; Austford, Leslie D.; Roman, Michael A.; et al.
Abstract : Purpose: To examine the feasibility of screening for chronic obstructive pulmonary disease (COPD) in an outpatient cardiac rehabilitation (CR) setting and to evaluate the detection rate of COPD using a targeted screening protocol. Methods: A total of 95 patients (62.5 ± 10.0 yr; men, n = 77), >40-yr old with a history of smoking were included in the study sample. Each participant answered the 5-item Canadian Lung Health Test (CLHT) questionnaire assessing symptoms such as coughing, phlegm, wheezing, shortness of breath, and frequent colds. Endorsing ≥1 item was indicative of potential COPD and warranted pulmonary function testing (PFT) and/or spirometry to diagnose or rule out COPD. Results: The CLHT questionnaire identified 44 patients at risk for COPD, with an average of 1.9 ± 1.2 items endorsed. Of the patients who underwent PFT, 6 new cases of mild COPD were diagnosed, resulting in a true positive rate with CLHT screening of 19% and a false-positive rate of 81%. Conclusions: Implementing the CLHT to patients referred to CR correctly identified COPD in <20% of cases. Using the CLHT to screen for COPD prior to starting CR may not be optimal, due to disparities between true- and false-positive rates. Abstract : Supplemental Digital Content is Available in the Text.The Canadian Lung Health Test (CLHT) questionnaire was used to screen for chronic obstructive pulmonary disease (COPD) in patients starting cardiac rehabilitation (CR). It yielded true- and false-positive rates of 19% and 81%, respectively. Applying the CLHT to screen for COPD before CR may not be optimal.